Photochemistry Past, Present and Future - Albini, Angelo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This anthological description of the history and applications of photochemistry provides photochemistry practitioners with complementary information about the field, currently not covered in existing textbooks and handbooks. Divided into two sections, the first part focuses on the historical development of the field, including light-matter interaction, the discovery of photochemical reactions and the development of modern photochemical mechanisms. This section provides useful background to the second part which outlines applications of photochemistry in the present day, such as in synthesis, green chemistry, diagnostics, medicine and nanotechnology. Furthermore, the author provides an outlook on promising areas for future developments. The broad scope of "Photochemistry: Past, Present and Future" is also of interest to the wider chemical audience and it makes a pleasant read while not compromising on scientific rigor.
Early Times of Photochemistry -- The Framework of Photochemistry: The Laws -- The Framework of Photochemistry: State Diagram -- Some Paradigmatic Topics -- The Role of Photochemistry in Chemistry -- Photochemistry, a Powerful Science -- Of Excited States, Again -- Photochemical and Photocatalyzed Synthesis -- Medicinal and Diagnostic Applications -- Solar Energy Conversion -- Actuators -- Photochemistry and Green Chemistry.
Keywords: Physical chemistry; Physical Chemistry